Iztēle lasītprasmes apguvei latviešu valodas stundās 1.klasē - Civkore, Mārīte (Latvijas Universitāte, 2007)
Diplomdarba nosaukums ir „Iztēle rakstītprasmes apguvei latviešu valodas stundās 1. klasē”. Diplomdarbā atklāts, ka mācību process norit radošāk, ja pedagogs padara to emocionālāku, interesantāku, iesaistot iztēli, atmiņu, domāšanu. Iztēle darbojas ar tēlu un priekšstatu, asociāciju ķēdēm. Sākumskolā bērniem raksturīga reproduktīvā iztēle, iztēlē izpaužas radošs raksturs. Rakstītmācības procesā iekļaujot ilustratīvi praktiskus, daudzveidīgus rakstu vingrinājumus ar iztēles elementiem, var veicināt skolēnu rokraksta un pareizrakstības attīstību. Atslēgas vārdi: -iztēle, jaunu tēlu veidošana, pamatojoties uz iepriekš uztvertajiem; -rakstītprasme, doma darbībā; -rakstītprasmes apguve, mācība; -latviešu valoda kā priekšmets skolā, iztēles vingrinājumi.

The title of the work is “Imagination for writing skills mastering in Latvian language lessons in 1. class”. The learning process is more creative if a pedagogue is making it more emotional, interesting, by involving the imagination, memory and thinking. About these matters many publications from different authors could be found. The imagination is acting with chains of personage, concepts and associations. It has a great role in development of the abstract thinking. Imagination and figurative thinking is connective to the dreaming and is more characteristic to children. The dreaming also could be as a self protecting mechanism, when the traumatizing information an infant is modifying to the fantasy thus minimising its influence to the psyche. With the imagination are linked also the drawings. The appearing of points in the drawings means that an infant is starting to understand that there is tight link between reality and a pencil’s facilities to reproduce it. The reproductive imagination is more characteristic for the infants, when the most part of infants is following to the learned etalons, according to the experience. In the imagination the creative character becomes apparent. The goal of the diploma paper – to find out the use of imagination in writing skills mastering process in Latvian language lessons at 1. classes. The object of investigation - The use of imagination for youngest age school infants in pedagogical process. The diploma paper consists of three parts. The first part summarizes the cognitions about imagination and its development possibilities for youngest age school infants in pedagogical process of different pedagogues and psychologists. In the second part the author analyses the methodical literature about writing skills as the part of the learning of Latvian language. In the third part the practical work has been done – the imaginations use in writing skills, the analysis of the results. The base of the practical work. 17 infants from a Riga secondary school.
Imagination for literacy acquisition in the Latvian language lessons in Grade 1
Keywords: Pedagoģija